Carbon Monoxide as a Signaling Molecule in Plants - Wang, Meng; Liao, Weibiao (Frontiers in Plant Science, 2016)
Carbon monoxide (CO), a gaseous molecule, has emerged as a signaling molecule in plants, due to its ability to trigger a series of physiological reactions. This article provides a brief update on the synthesis of CO, its physiological functions in plant growth and development, as well as its role in abiotic stress tolerance such as drought, salt, ultraviolet radiation and heavy metal stress. CO has positive effects on seed germination, root development, and stomatal closure. Also, CO can enhance plant abiotic stress resistance commonly through the enhancement of antioxidant defence system. Moreover, CO shows cross talk with other signaling molecules including NO, phytohormone (IAA, ABA and GA) and other gas signaling molecules (H2S, H2, CH4).